Medical education and health care in China and the USA: a follow-up study of a 4 year cardiovascular visiting programme between Peking University and the University of Minnesota. (December 2017) - She, Jianqing; Liao, Kenneth
Abstract: Background: China has witnessed a fast-developing social system in the past decades; meanwhile, its medical education and health-care system still face many challenges. A growing number of exchange programmes are being established to promote mutual awareness of medical education and health-care systems. The cardiovascular visiting programme between Peking University and University of Minnesota was established in 2013. The aim of this study was to investigate participating Chinese students' opinion about differences in medical education and health care between China and the USA. Methods: We interviewed Chinese visiting medical students about the difference in health education and medical system between China and the USA before and after their visit to the USA. The questionnaire was based on three parts: the major difference in medical education; the strongest differences in residency training; and major challenges of medical status in China. Findings: We interviewed 17 Chinese medical students. When comparing various aspects of the Chinese and American health education and medical systems, most students (91%) thought that China's medical education system placed highest value on textbook learning, and all students (100%) believed self-learning to be most important in the USA. Many students (76%) also believed that clinical skill training drew more attention in the USA than in China. Compared with Chinese hospitals, most participants responded that American hospitals obtained the more advanced clinical equipment (76%) and paid more attention to evidence-based treatment (100%), disease prevention (94%), and the importance of a national informationised system (65%). Among the challenges China is facing, amendment of the national medical referral system, improvement in doctor income and freelance policy, and strengthened clinical skills and operations training during fellowships were considered more important and urgent than in the USA. Interpretation: We found various differences between China and the USA with respect to medical education, hospital management, medical insurance, and communication between the patients and doctors. China still faces challenges and gaps in its health education and hospital management system as compared to the USA. As a result, mutual exchange programmes for medical students between China and the USA are beneficial and a crucial way to achieve a global and prosperous medical development in the future. The biggest limitations of this observational study were its small sample size and that it included Chinese students only. More medical students from both China and the USA might be interviewed in the future so as to further explore the difference in the medical education system. Funding: None.